Nicholas Moussis. Access to European Union. Law, economics, policies, Rixensart: Study Service, 1999. 9th revised edition, 584 s.; Nicholas Moussis. Handbook of European Union. and policies, Rixensart: European Study Service, 1998, 51'1revised edition. 36 - Chr. Sidenius, Niels (Politica, 2000)
Nicholas Moussis. Access to European Union. Law, economics, policies, Rixensart: Study Service, 1999. 9th revised edition, 584 s.; Nicholas Moussis. Handbook of European Union. and policies, Rixensart: European Study Service, 1998, 51'1revised edition. 360 s.